Carbon neutrality through supply chain performance: does green innovation matter in Asia?. Issue 3 (25th December 2023) - Liu, Linlin; Wu, Hong; Hafeez, Muhammad; Albaity, Mohamed Shikh Abubaker; Ullah, Sana
Abstract: Logistics performance is considered an important determinant of supply chain performance that results in carbon neutrality. The main aim of this study is to investigate the influence of logistics performance and green innovation on carbon emissions for selected Asian economies over the period 2007–2020. The 2SLS approach has been employed for empirical tasks, and the robustness of results has been confirmed through the GMM approach. The results indicate that logistics performance significantly reduces carbon emissions. Besides the logistics performance index, five other indicators of logistics performance have been used in the analysis. These indicators include quality of logistics services, tracking and tracing capability, logistics infrastructure quality, cargo transportation timelines, and customs clearance efficiency. All these indicators are negatively correlated with carbon emissions. The results further indicate that green innovation leads to a significant reduction in carbon emissions. Thus, our results emphasize the priorities of green innovation, logistics performance, and environmental sustainability in Asian economies.